The Effect of Fertilizer use on Nitrate and Metal Content in Dong Du Mustard Green (Brassica campestris L.) - Thi Hoang Oanh, Le; Dang Anh, Nguyen; Van Quang, Pham; Huu Huan, Nguyen; Ha, Nguyen Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2SDO - 10.25073/2588-1094/vnuees.5414, 2025)
Fertilizers are widely used in farming, contributing to improving crop productivity and quality. However, the uncontrolled use of fertilizers in vegetable production may cause consequences on the environment, crops, and human health. This study evaluated the effects of fertilizer use on nitrate and metal content in Dong Du mustard green ( Brassica campestris L.). The effects of fertilizers were analyzed for different fertilizer types, nitrogen content, quantity, and fertilization regime on the field scale in Me Linh, Hanoi. Nitrate content in Brassica campestris L. ranged from 47 to 344 mg/kg when applying the studied fertilizer formulas, which was lower than the limits in Decision 99/2008 of the Ministry of Agriculture and Rural Development for plants of the same family Brassicaceae and the average limit from Circular 68/2010 of the Ministry of Agriculture and Rural Development for on food safety limits. The Cd and Pb contents fluctuated at 0.05-0.13 mg/kg and 0.99–3.26 mg/kg in this vegetable, respectively, which were both higher than the limits prescribed by safe vegetable standards (according to CODEX STAN 193-1995). The study demonstrated the level of safety of the studied fertilizer formulas in the production of Dong Du mustard green in term of nitrate accumulation.